New proton conductive membranes of indazole- and condensed pyrazolebisphosphonic acid-Nafion membranes for PEMFC - Teixeira, Fatima (2022)
ABSTRACT: In this work, new doped Nafion membranes for PEMFC are prepared by casting with 1 wt% loading of the prepared indazole- and condensed pyrazolebisphosphonic acids (AzBPs). The new membranes were analysed by ATR-FTIR spectroscopy and their morphology was examined by SEM. Membranes were evaluated for water uptake and ion exchange capacity (IEC), and their hydration number was estimated. The proton conduction properties of the modified membranes were evaluated by electrochemical impedance spectroscopy (EIS), at different temperatures (30, 40, 50 and 60 °C) and relative humidity (RH) (40, 60 and 80%). The proton conductivities of all membranes increase with increasing temperature and RH. Also, all new membranes doped with AzBPs exhibited higher proton conductivities than Nafion N-115, used as a reference and tested at the same experimental conditions, with values up to 1.5-fold. Results show that the incorporation of AzBPs dopants on Nafion membranes enhances the proton conduction throughout the modified membranes. The best proton conductivity was observed for membranes with AzBP1 as dopant, with a value of 94 mS cm-1. These results indicate that the Nafion membranes doped with indazole- and condensed pyrazolebisphosphonic acids are a promising approach for new membranes for PEMFC with improved proton conductivity.